Strategic Synergy: Integrating Food Security and National Defense to Mitigate Global Threats - Aris Sarjito (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The integration of food security and national defense is critical in addressing global threats that endanger national resilience. This research examines the current practices and challenges in merging these policies across various countries, aiming to develop a comprehensive framework for strategic synergy. Using qualitative research methods, this study analyzes secondary data from government reports, academic literature, and international organizations. Findings indicate that while some nations have successfully integrated food security and defense strategies, many face challenges such as policy misalignment, resource constraints, and lack of coordination among stakeholders. The impact of integrated policies on national resilience is significant, enhancing a country's ability to withstand global threats such as pandemics, climate change, and geopolitical instability. This research proposes a robust framework for integrating food security and national defense strategies, emphasizing the importance of interagency collaboration, resource optimization, and adaptive policy-making. In conclusion, the strategic synergy between food security and national defense is essential for strengthening national resilience and ensuring sustainable development.